Blockchain and smart contracts : design thinking and programming for FinTech - Lo, Swee Won; Wang, Yu; Lee, David Kuo Chuen (Singapore : World Scientific Publishing Co. Pte. Ltd., 2021)
'Innovative as it is, the blockchain technology is getting more and more attention and an increasing number of applications have emerged. This book elaborates on both the design thinking ideas and technical details in blockchain and smart contracts to help readers delve into the conceptual framework and understand why blockchain is designed as such and how it makes the current system decentralised yet effective. Having this understanding lays the ground for further analysis of blockchain-based solutions and innovative fintech applications. Topics covered in this book include blockchain structure, blockchain ecosystem, design thinking for blockchain, smart contract, fintech and financial services, solution-based problem solving, fintech valuation, and current issues faced such as privacy protection and solution selection, with the aid of real-life examples and hands-on exercises. Blockchain and Smart Contracts serves as a valuable guide for researchers and practitioners who have interests in the blockchain, smart contract, fintech innovation and applications, design thinking, and technical details. This book is particularly written for anyone who has no technical background and is searching for an initiation into the deep end of blockchain. Those with business, finance and economic interests will find this interesting and easy to digest'--
Cryptography in Blockchain -- Bitcoin Mining and Python Programming Demonstration -- Consensus for Blockchain and Distributed Ledger Technologies -- Token Economics and Valuation -- Cryptocurrency as an Alternative Investment Class -- A Look at Security and Privacy: Bitcoin, Cryptocurrencies and Blockchain -- Networks -- Introduction to Blockchain Smart Contracts and Programming with Solidity forEthereum -- Hands-On Lab with MultiChain -- Hands-on Guide to Bitcoin Layer 2 Lightning Network Node Setup -- Architecting and Designing Your Own Blockchain Solution.
Includes bibliographical references and index.
Keywords: Blockchains (Databases) -- Design and construction; Computer programming; Cryptocurrencies; Computer security